Ocorrência de aflatoxina em pastas de amendoim (Arachis hypogaea L.) - Fonseca, Homero; Nery, Humberto Del (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1970)
In the present work, the Authors studied the incidence of aflatoxin in 30 samples of peanut butter, (Arachis hypogaea, L.) beeing 10 from a Brazilian factory (A), 10 from another Brazilian factory (B) and 10 of 7 brands from U.S.A. The extraction of aflatoxin was made with chloroform, separated by thin-layer chromatography with Silicagel-G and quantified under an ultra-violet lamp. The results showed that only 3 samples (10%) were free from aflatoxin and were of U.S. origin; 6 (20%) had them under 0,05 ppm; 15 (50%) were between 0,05 and 0,25 ppm; 5 (16,6%) between 0,25 and 1,00 ppm. and 1 (3,3%) more than 1,00 ppm. These values express the total toxicity in terms of B1. The Authors have concluded that of the Brazilian samples, only 3 were in a condition for beeing consumed, and those still with some restrictions. They pointed out that one sample of the Factory B, have showed a very high level of aflatoxin.